Key actors in driving behavioural change in relation to on-farm biosecurity; a Northern Ireland perspective - Lahuerta-Marin, A.; Brennan, M.L.; Finney, G.; O’Hagan, M.J.H.; Jack, C. (BioMed Central, 2018)
Background: Agriculture and farming are valued contributors to local economy in Northern Ireland (NI). There is limited knowledge about farmers’ behaviours and attitudes towards disease biosecurity measures. As part of a larger project, a scenario-based workshop with key stakeholders was organised by the Agri-Food and Biosciences Institute (AFBI)-NI in December 2015. Results: A total of 22 participants belonging to 12 different institutions took part in the workshop. Participants were presented with an overview of previously conducted biosecurity research in NI and England. In small groups, participants were subsequently asked to discuss and give their opinions about a series of questions across four key areas in a semi-structured approach with an external facilitator. The key areas were 1- disease risk perception at the farm level; 2-perceived barriers to implementing on farm biosecurity measures; 3- avenues to successful behaviour change and 4-key industry responsibilities and roles. The discussion showed that training in biosecurity for farmers is important and necessary. Training was recommended to be provided by veterinary surgeons, preferably via a face-to-face format. The discussion addressing disease disclosure proved particularly challenging between those who were prospective buyers of cattle, and those who sold cattle. Conclusions: This workshop provided a unique and invaluable insight into key issues regarding farm level biosecurity activities. From a policy perspective, delivering improved on-farm biosecurity must be addressed via a multidisciplinary approach. This can only be achieved with active involvement, commitment and support of a number of key industry and government stakeholders.